2014
DOI: 10.1158/1078-0432.ccr-13-2620
|View full text |Cite|
|
Sign up to set email alerts
|

Cabozantinib Suppresses Tumor Growth and Metastasis in Hepatocellular Carcinoma by a Dual Blockade of VEGFR2 and MET

Abstract: Purpose: MET signaling has been suggested a potential role in hepatocellular carcinoma (HCC) and associated with prometastasis during antiangiogenesis therapy. We investigated the potential association between MET expression and therapeutic response to sorafenib in patients with HCC. Antitumor effects of cabozantinib, a dual inhibitor of MET and VEGFR2, were examined in cultured HCC cells as well as in vivo models.Experimental Design: Total MET and phosphorylated MET (p-MET) were measured in 29 resected HCC sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(172 citation statements)
references
References 38 publications
5
159
0
3
Order By: Relevance
“…Cabozantinib (XL184), a dual blockade of VEGFR2 and MET, inhibited tumor growth in HCC by decreasing angiogenesis, inhibiting proliferation and promoting apoptosis, but it exhibited more profound efficacy in phosphorylated-MET positive HCC xenografts [88] . A phase Ⅲ study of cabozantinib vs placebo in HCC patients who have received prior sorafenib (NCT01908426) is ongoing.…”
Section: Treatment Of Hccmentioning
confidence: 99%
“…Cabozantinib (XL184), a dual blockade of VEGFR2 and MET, inhibited tumor growth in HCC by decreasing angiogenesis, inhibiting proliferation and promoting apoptosis, but it exhibited more profound efficacy in phosphorylated-MET positive HCC xenografts [88] . A phase Ⅲ study of cabozantinib vs placebo in HCC patients who have received prior sorafenib (NCT01908426) is ongoing.…”
Section: Treatment Of Hccmentioning
confidence: 99%
“…In separate experiments in naïve mice, cabozantinib treatment inhibited phosphorylation of MET by HGF in liver tissue and phosphorylation of VEGFR2 by VEGF in lung tissue. Consistent with this activity, significant tumor growth inhibition or tumor regression after cabozantinib treatment has been observed in multiple tumor xenograft models including medullary thyroid cancer (MTC), breast cancer, hepatocellular carcinoma, lung carcinoma, and glioblastoma [13,22,23]. In a phase 3 trial, cabozantinib demonstrated efficacy compared with placebo in progressive, metastatic MTC, leading to approval in this indication [24].…”
Section: Preclinical Development and Rationalementioning
confidence: 80%
“…And also, more complicated mechanisms still require further study by obtaining co-crystal structures of P-gp to explain the involving functional modulation of psoralen. 20) In recent years, many studies have found that MCF-7/ ADR with over-expression of P-gp showed stronger invasive ability and malignant potential compared to parental control MCF-7 cell possibly related to the loss of E-cadherin expression which is the epithelial marker. 21) This process is essentially dependent on the prominent biological event referred to as EMT 22,23) which enables cells of epithelial phenotype to generate mesenchymal derivatives.…”
Section: Discussionmentioning
confidence: 99%